ARTIFICIAL INTELLIGENCE IN CYBERSECURITY: THREATS, DEFENSES, AND FUTURE DIRECTIONS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
This study explores the usage of Artificial Intelligence and machine learning technology in modern cybersecurity. When cyberattacks becoming more frequent, organizations are turning to AI-powered solutions to improve their defense systems. Adoption of AI technologies like machine learning and deep learning is shown to improve the accuracy of threat detection, but data reliability, model interpretability, and bias in decision-making systems remain significant issues. Research has proven AI to be most successful in preventing large-scale attacks, i.e., DDoS, through the recognition of patterns in network traffic based on models like Recurrent Neural Networks (RNNs) and Convolutional Neural Networks (CNNs). The application of AI technologies, such as machine learning and deep learning, has been shown to improve the speed and precision of threat detection so that it becomes easier to identify and counteract previously unknown vulnerabilities. Despite these advantages, very low rates of organizations have fully implemented AI-driven security solutions, and confidence in AI decision-making still affects deployment. This article also highlights increasing incidents of AI-driven cyber attacks, such as AI-created malware, automated phishing, and deepfake identity theft, that are outrunning traditional security controls. This analysis also emphasizes the growing importance of application of AI in cybersecurity with underscoring its potential to strengthen defens systems against zero-day attacks and similar evolving threats. However, it also reviews some of the challenges that need to be addressed for more effective integration of AI models in cybersecurity, such as the reliability of the data that is being used for its' training. With the development in AI technologies, machine learning based models are expected to play an increasingly crucial role in protection of both businesses and individuals from sophisticated cyberattacks. And despite all the advantages, the full implementation of AI-driven security solutions remains low. What is more, concerns about the trustworthiness of AI decisions and the lack of transparency in AI models still remains.